Chemotherapy of Buxtonella sulcata in cattle in Sanandj, Iran - Hasheminasab, Seyed sajjad; Darbandi, Meysam Sabour; Talvar, Hadi Mohammadi; Maghsood, Hossein; Khalili, Sara (International Journal of Medicine, 2015)
Parasitic nematodes are one of the most important causes of production losses in most cattle-producing countries of the world. The aim of the present study Chemotherapy of B. sulcate in cattle in the Sanandj (Iran). The overall comparative efficacy of oxytetracycline and metronidazole was 66% and 32% respectively.